Suction drainage: a new approach to the treatment of empyema. Issue 4 (April 1991) - Cummin, A R; Wright, N L; Joseph, A E
Abstract : Thirteen patients with empyema thoracis were treated with a new suction drainage technique. The method entails passing a catheter into the empyema cavity under ultrasound guidance and using strong suction to drain loculated pus. Eight patients had no recurrence after a single treatment and one patient had no recurrence after two treatments. The procedure was a useful palliative measure in two patients with malignant disease who subsequently died. In one patient failure of the lung to expand after the procedure showed the need for thoracotomy. In one other patient the empyema recurred and decortication was required.